Pengaruh Promosi dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan (Studi pada Unit Mikro Bank Syariah Mandiri Medan Pulo Brayan) - Safii Siregar (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2021)
This study aims to analyze the effect of promotion and customer satisfaction on customer loyalty at the Syariah Mandiri Bank Micro Unit Medan Pulo Brayan, either partially or simultaneously. The types of data used are primary data and secondary data, the instruments (tools) for collecting research data used are questionnaires and interviews. The population in this study is an infinite number of customers at Bank Syariah Mandiri Medan Pulo Brayan Branch, while the sample is 100 customers, the sampling technique used is nonprobability sampling, using purposive sampling technique, namely sampling technique with certain considerations and criteria. . The data analysis technique is multiple linear regression analysis. The results showed that partially, each promotion variable and customer satisfaction has an effect on customer loyalty. Simultaneously, promotion and customer satisfaction variables affect customer loyalty at the Micro Unit of Bank Syariah Mandiri Medan Pulo Brayan